ANALISIS RASIO LIKUIDITAS, RENTABILITAS DAN SOLVABILITAS UNTUK MENILAI KINERJA KEUANGAN PT BAKRIE SUMATERA PLANTATIONS, Tbk - Zakaria Hamzah, Zeze; Nurjanah, Resti (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2018)
The purpose of this study was to determine the financial performance of PT Bakrie Sumatera Plantations, Tbk based on the Liquidity, Rentability and Solvability Ratios for the period 2012-2016. This type of research is quantitative descriptive using secondary data. This research was conducted by tracking data on the Indonesia Stock Exchange (IDX). The object of this research is the financial statements of PT Bakrie Sumatera Plantations, Tbk. The results showed that Financial Performance based on liquidity ratios, Current Ratio decreased from 1.26 to 0.09, Cash Ratio decreased from 0.040 to 0.006 and Quick Ratio decreased from 1.18 to 0.09. Based on the profitability ratio, the condition of the company is in a bad condition, because Gross Profit Margin has decreased by 0.30 to 0.25 and the Net profit margin has suffered losses from -0.38 to -0.52. Likewise based on solvency ratio, in a bad condition because Debt to Equity Ratio has increased from 0.58 to 0.92 and the value of Debt to Total Assets Ratio is higher than 1.4 to 11.27.